2017
DOI: 10.17576/jsm-2017-4604-06
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selected Herbs and Vegetables on the Nutritional Quality of Beef Burger and Rat Bioassay

Abstract: Rat bioassay was used to evaluate the nutritional quality of beef burger as influenced by the addition of selected herbs and vegetables. The selected herbs and vegetables used were pucuk ubi (Mannihot esculenta), pucuk gajus (Anacardium occidentale), pegaga (Centella asiatica)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The spinach incorporation affected (p < 0.001) the proximate composition, energy content, and sodium amount. As commented above, the reduction of fat content in meat products has been studied by several authors (Afshari, Hosseini, Khaneghah, & Khaksar, 2017; Heck et al, 2017;Khalid et al, 2017;Lorenzo, Pateiro, Fontán, & Carballo, 2014). In our study, control burgers showed the highest fat content (7.49%), decreasing the fat content with the increasing of the spinach amount in the burger formulation (6.48% and 5.76%, for E10 and E30 groups, respectively).…”
Section: Proximate Compositionsupporting
confidence: 71%
“…The spinach incorporation affected (p < 0.001) the proximate composition, energy content, and sodium amount. As commented above, the reduction of fat content in meat products has been studied by several authors (Afshari, Hosseini, Khaneghah, & Khaksar, 2017; Heck et al, 2017;Khalid et al, 2017;Lorenzo, Pateiro, Fontán, & Carballo, 2014). In our study, control burgers showed the highest fat content (7.49%), decreasing the fat content with the increasing of the spinach amount in the burger formulation (6.48% and 5.76%, for E10 and E30 groups, respectively).…”
Section: Proximate Compositionsupporting
confidence: 71%
“…On the nutritional front, there is limited research in assessing the nutritional value of these WEPs consumed by the Orang Asli, though there has been a resurgence of interest in the significance of these plants in sustaining indigenous communities worldwide [ 13 ]. In contrast, the corpus of knowledge is more sizable on “ulam” (type of Malay traditional salad that is made from fresh vegetables, fruits, and leaves and is usually consumed raw or after steeped in hot water), which is consumed by the dominant population [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%